Cultural Conceptualization in Proverb: Cultural Linguistic Study - Ermitati, Ermitati (Salingka, 2022)
Language and culture have a very close relationship because a language is used by its speakers to realize the conceptualization of their culture. This has resulted in various cultural conceptualizations created as a result of interactions between members of cultural groups encoded in various features of the Indonesian language. This paper discusses issues related to (a) How is the form of cultural conceptualization encoded in proverbs, in particular, ibarat in Indonesian language? (b) How do Indonesian speakers conceptualize the culture they have? This research data was collected through literature study and using written data sources in the form of works proverb books, and using listening techniques and note-taking techniques. Data were analyzed using cultural linguistic theory proposed by Sharifian (2017), which states that Cultural Linguistics views the relationship between language, thought and culture as complex, dynamic, and multidirectional, with human conceptual abilities acting as active agents mediating between cultural experience and human language experience. This paper finds five types of conceptualization in the Indonesian language, namely (a) Conceptualization of Culture Related to Character and Morals, (b) Conceptualization of Culture Related to Human Conditions, (c) Conceptualization of Culture Related to Waste of Action, (d) Conceptualization of Culture relating to Unrealized Desires, and (e) Conceptualization of Culture Related to Suffering caused by OthersAbsrakBahasa dan budaya memiliki hubungan yang sangat erat karena bahasa digunakan oleh penuturnya untuk mewujudkan konsepualisasi budaya yang mereka miliki.  Hal itu menyebabkan  berbagai konseptualisasi budaya yang  tercipta sebagai hasil interaksi antara anggota kelompok budaya tersandi dalam berbagai fitur bahasa Indonesia. Tulisan ini membahas masalah yang berkaitan dengan (a) Bagaimana bentuk konseptualisasi budaya yang tersandi dalam peribahasa, khususnya, ibarat bahasa Indonesia? (b) Bagaimana cara penutur bahasa Indonesia mengonseptualisasikan budaya yang mereka miliki? Data tulisan ini dikumpulkan melalui studi pustaka dan menggunanakan sumber data tertulis berupa buku peribahasa karya, serta menggunakan teknik simak dan teknik pencatatan. Data dianalisis menggunakan teori linguistik budaya yang dikemukakan oleh Sharifian (2017), yang menyatakan bahwa Linguistik Budaya  memandang hubungan antara bahasa, pemikiran, dan budaya sebagai sesuatu yang kompleks, dinamis,  dan multidireksional, dengan kemampuan konseptual manusia yang bertindak sebagai agen aktif yang memediasi antara pengalaman budaya dan pengalaman bahasa manusia. Tulisan ini menemukan lima jenis konseptualisasi yang terdapat dalam ibarat bahasa Indonesia, yakni (a) Konseptualisasi Budaya Yang Berkaitan dengan Karakter dan  Moral, (b) Konseptualisasi Budaya yang Berkaitan dengan Keadaan Manusia, (c) Konseptualisasi Budaya yang Berkaitan dengan Perbuatan Sia-Sia, (d) Konseptualisasi Budaya yang berkaitan dengan Keinginan yang Takmungkin Terwujudkan, dan (e) Konseptualisasi Budaya yang Berkaitan dengan Penderitaan yang disebabkan oleh Orang lain.